2013
DOI: 10.1371/journal.pone.0064216
|View full text |Cite
|
Sign up to set email alerts
|

Activated Eosinophils in Association with Enteric Nerves in Inflammatory Bowel Disease

Abstract: Enteric neural dysfunction leads to increased mucous production and dysmotility in inflammatory bowel disease (IBD). Prior studies have shown that tissue eosinophilia is related to disease activity. We hypothesized that interactions between eosinophils and nerves contribute to neural dysfunction in IBD. Tissue from patients with intractable IBD, endoscopic biopsies from patients with steroid responsive IBD, both when active and quiescent, and control tissue were studied. Immunohistochemical studies showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 67 publications
3
30
0
Order By: Relevance
“…Support for a functional role for eosinophils is found in animal studies, where mice lacking eosinophils, eotaxin or eosinophil granule proteins have diminished intestinal inflammation [63][64][65]. A recent study has shown that eosinophils, optimally quantified with a specific antimajor basic protein immunostaining, are increased in the lamina propria of IBD patients in numbers correlating with disease severity [66]. Furthermore, a careful morphological description of eosinophil tissue distribution revealed localization to mucosal nerve fibers.…”
Section: Inflammatory Bowel Diseasementioning
confidence: 94%
See 1 more Smart Citation
“…Support for a functional role for eosinophils is found in animal studies, where mice lacking eosinophils, eotaxin or eosinophil granule proteins have diminished intestinal inflammation [63][64][65]. A recent study has shown that eosinophils, optimally quantified with a specific antimajor basic protein immunostaining, are increased in the lamina propria of IBD patients in numbers correlating with disease severity [66]. Furthermore, a careful morphological description of eosinophil tissue distribution revealed localization to mucosal nerve fibers.…”
Section: Inflammatory Bowel Diseasementioning
confidence: 94%
“…The profile of cytokines produced by the TH2 CD4 + T-cell lineage selectively supports eosinophil recruitment and activation, a key feature of inflammation observed in the GI tract in several distinct pathologies. In both prototypical atopic diseases, such as asthma, and in more recently acknowledged eosinophil/ mast cell-associated diseases, including IBD, IBS and FD, the localization of these potent innate effector lineages in close proximity to mucosal nerve fibers offers a plausible mechanism for these cells to potentiate aberrant smooth muscle activation, which may culminate in inappropriate hyperactivity of the airways or indeed gut [66].…”
Section: Common Immune Pathways Linking Atopy and Gi Diseasementioning
confidence: 99%
“…Increased numbers of tryptase-IR mast cells have been already described in several diseases of the gastrointestinal tract, such as ulcerative colitis (Stoyanova and Gulubova 2002;Albert et al 2011;Stasikowska-Kanicka et al 2012), Crohn's disease (Raithel et al 2001;Christerson et al 2009;Smyth et al 2013), and chagasic megaesophagus (Martins et al 2014). Those disorders have in common an exacerbated inflammatory process, which could be maintained by high levels of tryptase.…”
Section: Discussionmentioning
confidence: 98%
“…15 Studies in patients with different forms of GI eosinophilic inflammation have shown increased numbers of activated eosinophils and increased concentrations of extracellular granule protein, suggesting that these cells may be important players in promoting and mediating inflammation in the intestinal mucosa. [29][30][31][32] Therefore, it is important to be able to reliably detect and quantify both intact and degranulated eosinophils in order to better understand their involvement and contribution to disease pathogenesis. In our previous study, enumeration of eosinophils after Epx mAb IHC indicated the presence of increased numbers of degranulated eosinophils in the upper and lower LP of the jejunum in dogs diagnosed with IBD compared with control dogs and dogs that had been treated for IBD.…”
Section: Discussionmentioning
confidence: 99%